2012
DOI: 10.1213/ane.0b013e31824c4ed4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Attenuates Neuropathic Pain and Cytokine Expression After Chronic Constriction Injury of Rat Sciatic Nerve

Abstract: These results suggest that progressive exercise training decreases peripheral neuropathic pain as well as TNF-α and IL-1β overproduction and increases HSP72 expression after CCI of the sciatic nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 38 publications
7
93
0
2
Order By: Relevance
“…The obtained results from this study showed that increased activity in the form of moderate endurance exercise can improve neuropathic pain responses in mechanical allodynia and thermal hyperalgesia. This result is consistent with some studies suggesting the significant effects of exercise training on neuropathic pain responses in various pain models (11,15). Conversely, some studies have failed to confirm the effects of exercise training on improvement of neuropathic pain (17).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained results from this study showed that increased activity in the form of moderate endurance exercise can improve neuropathic pain responses in mechanical allodynia and thermal hyperalgesia. This result is consistent with some studies suggesting the significant effects of exercise training on neuropathic pain responses in various pain models (11,15). Conversely, some studies have failed to confirm the effects of exercise training on improvement of neuropathic pain (17).…”
Section: Discussionsupporting
confidence: 91%
“…Exercise can also be accompanied by RNA biosynthesis, increased axonal transport, and increased neural sprouting followed by nerve cut (10). In contrast, the majority of observed sensory and motor nerves disorders in diabetic neuropathy are attributed to mitochondrial disorders in different parts of neurons, and multiple synaptic deficits (5,11,12). With regard to the involvement of neural motor proteins disorder in many of neurodegenerative diseases, so it is possible that they also have a role in loss of sensory and motor neurons caused by diabetic neuropathy disease.…”
Section: Introductionmentioning
confidence: 99%
“…In all three conditions, mechanical hyperalgesia was reduced compared with sedentary controls. However, the study, which was confirmed by a subsequent study, shows that exercise reduces local inflammatory mediators and nerve degeneration induced by the nerve injury (5,10). Thus the decrease in mechanical hyperalgesia in the nerve injury studies could be directly related to the decrease in inflammation and injury.…”
Section: Exercise Effects In Animal Models Of Painmentioning
confidence: 53%
“…The predominant exercise stimulus in animal studies of EIH are forced swimming 8,42,44,62 and treadmill, 10,53 which are considered stressful condition for rodents. 15,41,72 Stress is known to have an effect on pain behavior (increase or decrease), and the hypoalgesic effect demonstrated in these models may be a combination of EIH and the effect induced by stress.…”
Section: Effect Of Habituationmentioning
confidence: 99%